Synthesis and application of hexaallylamino-cyclo-triphosphazene as flame retardant in latex coatings - Machotová, Jana; Zárybnická, Lucie; Rückerová, Adéla; Bačovská, R.; Rychlý, J.; Imramovský, Aleš (My University, 2017)
The paper deals with a novel flame retardant and its application in waterborne coatings. The flame retardant was synthesized from hexachloro-cyclo-triphosphazene by nucleophilic substitution with allyl amine. Functionalized emulsion copolymers bearing in the structure hexaallylamino-cyclo-triphosphazene were prepared by the semi-continuous emulsion polymerization. The latexes were used as the main component of transparent coating systems cured by melamine-formaldehyde resin. The incorporation hexaallylamino-cyclo-triphosphazene did not affect transparency, flexibility and toughness of resulting coatings and increased their flame stability.
Syntéza a využití hexaallylamino-cyclo-trifosfazenu jako retardéru hoření v latexových nátěrech
Keywords: emulsion polymerization; core-shell latex; flame retardant; phosphazene; cone calorimeter; emulzní polymrace; core-shell latex; retardér hoření; fosfazen; cone kalorimetr